THE ROLE OF A CHARISMATIC LEADER IN WINNNING THE FIRST HALF OF THE CIVIL WAR AS SEEN IN GODS AND GENERALS MOVIE - Hidayati, Maulidini Wulan (LANTERN (Journal on English Language, Culture and Literature), 2014)
Gods and Generals movie is based on true story of the first half of the American Civil War (1861-1865). The aim of this thesis is to prove that the existence of a charismatic leader who is respected by his soldiers results in the victory for the Confederate States in the first half of the American Civil War based on Gods and Generals movie. The writer conducts the library research and sociology approach by applying the theory of role by Biddle & Thomas and charismatic leader theory by Max Weber. The result of this research is that General T.J “Stonewall” Jackson is a charismatic leader and he is able to give the victory to the Confederate States. A charismatic leader is a leader whose actively contributes in society, therefore he is respected